Cerebellar hemorrhage after embolization of ruptured vertebral dissecting aneurysm proximal to PICA including parent artery - Tamase, Akira (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Some complications related to vertebral artery occlusion by endovascular technique have been reported. However, cerebellar hemorrhage after vertebral artery occlusion in subacute phase is rare. In this report, we describe a patient who showed cerebellar hemorrhage during hypertensive therapy for vasospasm after embolization of a vertebral dissecting aneurysm. CASE DESCRIPTION: A 56-year-old female with a ruptured vertebral dissecting aneurysm proximal to the posterior inferior cerebellar artery developed cerebellar hemorrhage 15 days after embolization of the vertebral artery, including the dissected site. In this patient, the preserved posterior inferior cerebellar artery fed by retrograde blood flow might have been hemodynamically stressed during hypertensive and antiplatelet therapies for subarachnoid hemorrhage, resulting in cerebellar hemorrhage. CONCLUSION: Although cerebellar hemorrhage is not prone to occur in the nonacute stage of embolization of the vertebral artery, it should be taken into consideration that cerebellar hemorrhage may occur during hypertensive treatment.